2016
DOI: 10.4137/grsb.s40036
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of Protein Kinase Gene Expression in NK Cells from Chronic Fatigue Syndrome/Myalgic Encephalomyelitis Patients

Abstract: BACKGROUNDThe etiology and pathomechanism of chronic fatigue syndrome/myalgic encephalomyelitis (CFS/ME) are unknown. However, natural killer (NK) cell dysfunction, in particular reduced NK cytotoxic activity, is a consistent finding in CFS/ME patients. Previous research has reported significant changes in intracellular mitogen-activated protein kinase pathways from isolated NK cells. The purpose of this present investigation was to examine whether protein kinase genes have a role in abnormal NK cell intracell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 60 publications
2
19
0
Order By: Relevance
“…Interestingly, a recent study of gene expression in NK cells of CFS patients showed upregulation of RIPK3 [84], in line with the present data (Additional file 3: Table S3); this gene encodes a kinase that plays a vital role in inflammasomes and IL-1β signaling. However, a previous analysis of cytokine levels in the present material did not relieve any differences in CFS patients as compared to healthy controls [15].…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, a recent study of gene expression in NK cells of CFS patients showed upregulation of RIPK3 [84], in line with the present data (Additional file 3: Table S3); this gene encodes a kinase that plays a vital role in inflammasomes and IL-1β signaling. However, a previous analysis of cytokine levels in the present material did not relieve any differences in CFS patients as compared to healthy controls [15].…”
Section: Discussionsupporting
confidence: 91%
“…Following cytotoxic granule delivery to the immune synapse, the formation of perforin pores and granzyme-induced cell apoptosis are highly dependent on Ca 2+ (Orrenius et al, 2003 ; Voskoboinik et al, 2005 ). Previous studies have reported impaired Ca 2+ signalling in NK cells from CFS/ME patients demonstrated through changes to ERK1/2 and mitogen-activated protein kinase (MAPK) pathways (Chacko et al, 2016 ; Huth et al, 2016b ). CFS/ME patients have significantly decreased ERK1/2 following incubation with K562 cells (Huth et al, 2016b ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found that the mitogen‐activated protein kinase (MAPK/MEK1/2) pathway, including the extracellular signal‐regulated kinases (ERK1/2) and p38 signaling molecules, was impaired in CFS/ME and furthermore, that NK cells were significantly lower in cytoplasmic calcium than non‐CFS/ME, thus reducing intracellular signaling capacity through the ZAP‐70/Lck/phosphoinositide 3‐kinase (PI3K) pathway (Chacko et al. ; Huth et al. ; Nguyen et al.…”
Section: Discussionmentioning
confidence: 99%
“…); and (2) increased tyrosine kinase phosphorylation, calcium flux/signaling within the PI3K pathway, as the release of cytotoxic granules is calcium‐dependent (Chacko et al. ; Maher et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation